Galois groups and fundamental groups: 15.06. - 21.06.1997 - Harbater, David; Ihara, Yasutaka; Matzat, Bernd Heinrich (Tagungsbericht, 1997)
Shreeram S. Abhyankar; Mamoru Asada; Eva Bayer-Fluckiger; Elena Black; Irene Ingeborg Bouw; Jean-Marc Couveignes; Pierre Debes; Bruno Deschamps; Michael Dettweiler; Michel Emsalem; Wulf-Dieter Geyer; Robert M. Guralnick; Dan Haran; David Harbater; Yasutaka Ihara; Moshe Jarden; Gregor Kemper; Helmut Koch; Hendrik W. Lenstra; Pierre Lochak; Kay Magaard; Gunter Malle; Michel Matignon; Makoto Matsumoto; B. Heinrich Matzat; Shinichi Mochizuki; Peter F. Müller; Shoichi Nakajima; Hiroaki Nakamura; Florian Pop; Michel Raynaud; Stefan Reiter; Mohamed Saidi; Alexander Schmidt; Leila Schneps; Jean-Pierre Serre; Jack Sonn; Katherine F. Stevenson; John Swallow; Akio Tamagawa; Hiroshi Tsunogai; Montse Vela; Nuria Vila; Helmut Völklein; Stefan Wewers; Kay Wingberg; Anatoli V. Yakovlev; Pavel Alexandr. Zalesski; Michael Zieve